Legal Protection for BPJS Kesehatan Patients in Healthcare Services at the Dr. Soetomo General Academic Hospital Surabaya - Toyib, Muchammad; Yustianti, Surti; Kurnia, Sinarianda; Andriyanto; Nuri Herachwati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
This study explores the implementation of healthcare services for BPJS Kesehatan patients at Dr. Soetomo General Academic Hospital in Surabaya, Indonesia. The research objectives were to investigate patients' perceptions of the services provided, their understanding of rights and obligations, and the legal remedies available. Employing a juridical-empirical approach, the study surveyed 50 patients using qualitative data analysis. Findings revealed that 78% of patients considered the hospital's services good, despite some shortcomings such as inadequate drug information and attention from medical staff. Additionally, only 24% of patients were aware of their rights and obligations. Legal remedies within the hospital, handled by the Public Service Complaints Section, addressed patient complaints effectively, with approximately 12% of patients expressing dissatisfaction. However, non-litigation efforts through external organizations like the Indonesian Consumers Foundation were not reported. This study highlights the need for enhanced patient education and awareness, efficient complaint mechanisms, and further exploration of external legal recourse avenues to ensure comprehensive legal protection for BPJS Kesehatan patients.